THE STUDENTS’ COMPETENCE IN WRITING RECOUNT TEXT AT MAN 2 HALMAHERA UTARA - Alita Hasan; Roslan Muhammad (Universitas Khairun, 2022)
This study aims to determine the students' ability to write recount text, which was carried out in class X IPA1 at Madrasah Aliyah Negeri 2 North Halmahera in the 2021/2022 academic year as research subjects. This research was carried out for 1 day. This research is categorized as classroom action research. The author collaborates with an English teacher in carrying out this research. Classroom action research uses a discovery learning model. This research was conducted in only 1 cycle consisting of planning, action, observation and reflection. In obtaining the data the author uses qualitative methods, qualitative data is obtained through observation and interviews. The results showed that there were some students who did not understand changing verbs or auxiliary verbs in writing recount text. This can be seen from the results of students' writing tests in writing recount text. From the results of observations and interviews, it is known that there are some students who do not understand the change of verbs or auxiliary verbs in writing recount text.